Analisis Microteaching Mahasiswa PAI Universitas Sunan Giri Surabaya Pada Mata Kuliah Pendidikan Agama Islam - Insyirah, Ilusia; Muhammad Yusron Maulana El-Yunusi (CV. Satria Jaya, 2024)
The Postgraduate Islamic Education Study Program at Universitas Sunan Giri Surabaya in maintaining its commitment to advancing the quality of its graduates always tries to renew and update various strategies, so that the program and curriculum are always dynamic, this can be seen from several special programs such as microteaching for 3rd semester students whose benefits are extraordinary. The purpose of this study was to evaluate the ability of postgraduate students to teach PAI material to undergraduate students. This research uses a qualitative approach. Data collection techniques were conducted through interviews, observations, and documentation studies. Researchers conducted a process of data collection, data reduction, data presentation and the last step was conclusion drawing and verification. The results showed that 1) Evaluation of lecture material, it can be seen that there are still students who do not fully understand the material, this can be seen during discussion sessions with students. In the material on the relationship between the Qur'an and Science, in this session many students captured and understood the holy book of the Qur'an is a Divine Revelation that contains absolute truth from God and is always maintained in authenticity and integrity until the end of time, while in the material on the benefits of the Qur'an for humans many undergraduate students have not been able to understand the benefits of the Qur'an for humans in outline. 2) Evaluation of the situation and conditions during microteaching which includes strengths, weaknesses and obstacles and their solutions related to room conditions and the time of microteaching implementation.